Induced enzyme activities by acclimatised BAC-ZS mixed culture during the treatment of acid orange 7 [electronic resource] - Nadhirah Aminah Azizan, 1989- author; Zaharah Ibrahim, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2014